UKRAINIAN IT-INDUSTRY: TRENDS, CHALLENGES AND RESILIENCE DURING WAR - MYKHALCHYSHYNA, Larysa; DIACHUK, Yevhenii; NAKONECHNYI, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyses the state of development of the IT industry in Ukraine under martial law. It is emphasised that the IT sector plays a key role in Ukraine’s digital economy, ensuring effective data management, improving communications and supporting organisational processes. Ukraine occupies an important place in the global IT market and has been called the ‘Digital Tiger’. The main trends in the development of the IT industry are noted: an increase in the number of IT companies and individual entrepreneurs until 2023, followed by a slowdown in growth due to economic instability and war. The most popular KVEDs among industry players have been identified: 62 (‘Computer programming, consulting and related activities’) and 63 (‘Provision of information services’). The important contribution of the IT industry to Ukraine’s economy has been identified: in 2023, the IT ecosystem became the second largest export industry, accounting for 13.2% of total exports and 4% of GDP. However, in 2023, for the first time after six years of growth, there was a decline in IT exports. However, the IT industry remains an important pillar of the economy, demonstrating high resilience and adaptability during the war, and continues to strengthen its position in the digital and cyberspace. The article pays special attention to the impact of martial law on the IT industry. Most companies have successfully adapted to the new conditions, many have relocated, and most plan to return after the end of hostilities. The article identifies the main challenges for IT companies during the war: migration, business adaptation, mobilisation, security threats and financial constraints. The article highlights the importance and necessity of psychological support for IT professionals in wartime to maintain productivity and business sustainability. The article notes the active participation of IT professionals in supporting the army, cyber defence, and volunteer projects, as well as the launch of the B2B platform CodeUA to support cooperation between Ukrainian IT professionals and international clients. Thus, the Ukrainian IT industry is a stable source of foreign exchange earnings and contributes to the country’s digital security. In the future, it is necessary to focus on strategies for adapting business processes and maintaining the psychological state of IT professionals.